Constitutional Underpinning of Same-Sex Marriage in Kenya under Personal Law and Beliefs (Discourse of Law and Administration, 2026)
Human rights in Kenya are recognized by Article 19 of the Constitution to belong to each individual and that they are not granted by the state. As such, even though the state’s police power is preserved, the Constitution still entrenches the liberty of individuals against violence, inhuman and degrading treatment as well as psychological torture both from the public (state) and private sources (society). These entrenched rights are at the core of human dignity, which is also the basis of recognizing all human rights. In addition to liberty and human dignity, the Constitution also) recognizes the right to marry but limits it under Article 45(2 to persons of opposite sex. However, Article 45(4) mandates the recognition of other marriages concluded under personal law, traditions and systems of beliefs adhered to by those seeking to marry under them. Article 45(4) does not therefore limit such recognition to marriages contracted between persons of the opposite sex, unlike Article 45(2). The two sections are equally separated by a provision on equality of parties to a marriage, thereby restricting a consequential or conjunctive reading of the two as referring to only one and the same type of marriage. Such differential reading spurs a conflict as to whether same-sex marriage is either permissible only under Article 45(4) and not Article 45(2) or both. This tension is further convoluted by the prohibition of same sex conduct under Sections 162, 163, and 165 of the Penal Code. In order to resolve this legal gap, this paper proposes two approaches to entrenching marital rights to same sex individuals. The first approach is to adopt an interpretation that gives effect to Article 45(4) by recognizing the liberty of all individuals to marry a person of their choice as expressed under common law and in line with Article 20(3). The second approach is by employing the doctrine of constitutional penumbras through the interpretation of the right to liberty, privacy, expression, association and property so as to create shadows of the right of all individuals regardless of their sexual orientation to marry a person of their choice. To achieve this, this paper analyses the contents, nature and extent of the right to liberty and security of the person alongside notions of equal protection, due process and inherent dignity as understood in the American and Kenyan contexts. Based on the analysis of some of the recent decisions of Kenyan courts touching on homosexuality, this paper concludes that the same sex marital rights are entrenched in the constitution by virtue of common law and have been affected by the courts as freedom of association, liberty, non-discrimination and privacy.
Keywords: same-sex marriage; homosexuality; criminalization; constitutional penumbra; liberty; human dignity; privacy; family